A study to assess the effectiveness of buddy approach on knowledge regarding menstrual hygiene among adolescent girls in selected schools, Bengaluru - Dolma, Kelsang; M., Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Adolescence is a vital transition phase in human life, with menstruation being one of the most distinctive features. In India, menstruation in females can lead to the introduction of new vulnerabilities due to socio-cultural barriers. The sociocultural barriers often label periods as impure and have added stigma leading to ignorance of hygienic health practices. Methods: A pre-experimental research study was conducted among 60 adolescent girls who were divided into a researcher group and a buddy group studying in Adarsh Vidya Dhama, Bengaluru. The researcher group (30 older adolescent girls) was given planned teaching by the student researcher. Based on the post-test scores, five buddies were trained by the student researcher to disseminate information to the buddy group. Confidentiality was maintained throughout the study. Results: The findings of the study depict that, in the researcher group the mean post-test knowledge score is 16.23 which is higher than the mean pre-test scores of 11.87. The obtained ‘t’ value is -11.25 and the calculated p=0.000 (at p<0.05). Similarly, the mean post-test knowledge score after the buddy approach is 16.33 which is higher than the mean pre-test score before the buddy approach which is 11.40. The obtained ‘t’ value is -10.850 and the calculated p=0.000 (at p<0.05). Conclusions: Imparting knowledge of menstruation and menstrual hygiene using the buddy approach is cost-effective and impactful way to convey information. It promotes open communication often reaching more effectively than the professional health team.